The Impact of Terrarium Aesthetics on Purchase Behavior: A Binary Logistic Regression Analysis of The Celebes Plant Lover Community - Syahruni Aryanti; Jerry Heikal (Green Publisher Indonesia, 2026)
Terrariums have gained popularity as decorative elements that combine aesthetic value with low-maintenance plant care, particularly among urban and hobbyist communities. Understanding the factors that drive purchase decisions in such niche markets is essential for producers and marketers. This research aims to examine the factors influencing terrarium purchase decisions among members of the Celebes Plant Lovers community. The research employs a quantitative approach using binary logistic regression analysis based on data collected from 107 respondents. The independent variables include aesthetic appeal, type of terrarium, type of plant, maintenance, price, and purchasing platform, while the dependent variable is the purchase decision. The results show that the regression model is statistically significant (χ²(6) = 12.87, p = 0.045) and explains 18.2% of the variance in purchase decisions (Nagelkerke R² = 0.182), with an overall classification accuracy of 82.2%. Among the examined variables, only aesthetic appeal has a significant effect on purchase decisions (β = 0.965, p = 0.035), indicating that higher aesthetic value increases the likelihood of purchasing terrarium products. Other variables—such as type of terrarium, type of plant, maintenance, price, and purchasing platform—do not show significant effects. These findings highlight the importance of visual attractiveness in influencing consumer behaviour, particularly in hobby-based communities. The study contributes to the understanding of consumer decision-making by emphasizing the dominant role of aesthetics over functional and economic factors in niche markets.